THU0071 THE COMBINATION OF RHEUMATOID FACTORS WITH ANTIBODY SYSTEMS TARGETING CITRULLINATED, CARBAMYLATED AND PEPTIDYL ARGININE DEIMINASE AUTOANTIGENS DISTINGUISHES RHEUMATOID ARTHRITIS. (June 2019) - Dervieux, Thierry; Conklin, John; O'malley, Tyler; Brady, Kelley; Alexander, Roberta; Shi, Jing; Ibarra, Claudia; Mahler, Michael; Kremer, Joel; Weinblatt, Michael E.; Weinstein, Arthur
Abstract : Background: Novel antibody systems including anti-Carbamylated Protein Antibody (anti-CarP IgG) and anti-Peptidyl Arginine Deiminase Antibody (anti-PAD4 IgG) are emerging as independent diagnostic and prognostic biomarkers for Rheumatoid Arthritis (RA) (ref, 1-3). As such, these antibody systems may add value to rheumatoid factor (IgM) and anti-citrullinated peptide antibody (ACPA IgG), the hallmark antibodies in RA. Objectives: We evaluated the diagnostic performance of Rheumatoid Factor (RF) with antibody systems targeting citrullinated, carbamylated and PAD4 autoantigens in RA. Methods: The cohort consisted of 638 consenting subjects with RA (fulfilling the 1987 or 2010 ACR classification criteria, mean age: 59.8±0.5 years [SEM], 80% female) and a control group of 775 subjects (mean age: 44.7±0.5 years, 85% females, including Systemic Lupus Erythematosus [n=369], primary Sjogren's Syndrome [n=64], Primary Fibromyalgia [n=85], other connective tissue diseases [n=63], and a group of normal healthy donors [n=194]). Autoantibodies titers from serum were measured using fluoroenzyme immunoassays (anti-RF [IgM] and anti-CCP [IgG]; Phadia Upsala, Sweden), ELISA (anti-CarP [IgG], research use only [RUO], Inova Diagnostics, San Diego) and bead-based Aptiva TM technology (anti-PAD4 [IgG], RUO, Inova Diagnostics) in a clinical laboratory accredited by the College of American Pathologists. For each positive antibody (above each cutoff) a score of 1 was assigned and the cumulative presence of the 4 antibodies was determined [range 0-4]. The ability of the biomarkers to distinguish RA from controls was calculated using sensitivity, specificity and interval likelihood ratio (LR). Positive Predictive Value (PPV) was estimated at 10% pre-test probability. Statistics consisted of Mann-Whitney and Chi-square tests. Results: In this cohort anti-CarP IgG (>20 Units) yielded 33.5% sensitivity and 77.9% specificity. Anti-PAD4 (>1000 Units) yielded 35.0% sensitivity and 95.0% specificity. RF IgM (>5 Units/ml) and anti-CCP (>10 Units/ml) were 67.4% and 66.5% sensitive, respectively (87.5% and 97.0% specific, respectively). RA presented 5-fold higher 4-antibody system scores (2.02±0.05) than controls (0.42±0.02); (p<0.01). Scores greater than 2 yielded 42% sensitivity and 98.8% specificity. A total of 82 subjects presented with the full-house 4 antibodies (score = 4) while 81 of them had RA (99.9% specific). Interval LR and PV for each of the 4-antibody score are presented in the Table. There was no difference in the 4-antibody score between RA who fulfilled the 1987 ACR or 2010 ACR criteria (1.99±0.07 vs 2.08±0.09; p=0.40). In the subset of subjects newly diagnosed (less than one year), the average 4-antibody system score for RA (n=33) was 1.72±0.22 (36.3% with score greater than 2) and 0.58±0.12 for other diseases (0% with score greater than 2, 100% specific); (p<0.01). Conclusion: This cumulative combination of antibody systems targeting citrullinated, carbamylated, PAD4 and Fc autoantigens (RF IgM) is highly specific for RA. It may be useful in diagnosing and classifying RA even in symptomatic patients who present early in the course of disease. References: [1] Shi, et al. Proc Natl Acad Sci USA. 2011 108(42):17372-7 [2] Darrah E et al. Sci Transl Med. 2013 2;5186ra65 [3] Verheul, et al. Arthritis Rheumatol. 2018 Nov;70(11):1721-1731 Disclosure of Interests: Thierry Dervieux Shareholder of: Exagen (a diagnostics company not a pharmaceutical company), Employee of: Exagen (a diagnostics company not a pharmaceutical company), John Conklin Employee of: Exagen (a diagnostics company not a pharmaceutical company), Tyler O'Malley Employee of: Exagen (a diagnostics company not a pharmaceutical company), Kelley Brady Employee of: Exagen (a diagnostics company not a pharmaceutical company), Roberta Alexander Employee of: Exagen (a diagnostics company not a pharmaceutical company), Jing Shi Employee of: Exagen (a diagnostics company not a pharmaceutical company), Claudia Ibarra Shareholder of: Exagen (a diagnostics company not a pharmaceutical company), Employee of: Exagen (a diagnostics company not a pharmaceutical company), Michael Mahler Employee of: Inova Diagnostics (Not pharmaceutical, diagnostics company), Joel Kremer Shareholder of: Corrona, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Genentech, GSK, Lilly, Pfizer, Regeneron and Sanofi, Employee of: Corrona, Michael E. Weinblatt Shareholder of: Stock option: CanFite, Lycera, Scipher, Inmedix, Grant/research support from: Crescendo Bioscience, Bristol Myers Squibb, Sanofi, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, CanFite, Corrona, Crescendo, GlaxoSmithKline, Gilead, Horizon, Lilly, Lycera, Merck, Novartis, Pfizer, Roche, Samsung, Scipher, Set Point, Arthur Weinstein Shareholder of: Exagen (a diagnostics company not a pharmaceutical company), Consultant for: Exagen (a diagnostics company not a pharmaceutical company)